(untitled) (Baghdad Science Journal, 2019)
In this study, a total of 209 individuals of leeches were collected from Al-Hindyia River / Babil Province. 116 individuals were identified as Erpobdella octaculata (Linnaeus, 1758), 50 individuals as Erpobdella punctata (Leidy,1870) and 43 individuals as Hemiclepsis marginata (Müller, 1774). Four samples were collected monthly during a period from February to June 2018. Some physical and chemical water properties were also examined, including air and water temperature, potential of hydrogen pH, Electrical Conductivity EC, Total Dissolved Solid TDS, Dissolved Oxygen DO, and the Biological Oxygen Demand BOD₅. Air and water temperature were ranged 19.5-29, & 14.6-23.2 °C respectively. The values of pH ranged 6.2-7.6. EC ranged 1104-1581 μs/cm². The TDS recorded 669- 767 mg/l, while the DO reached 1.3- 8.5 mg / l, the BOD₅ ranged 3.5- 5.7 mg/l.